2011
DOI: 10.4196/kjpp.2011.15.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of ATP-sensitive K+ Channels Improves the Right Ventricular Tolerance to Hypoxia in Rabbit Hearts

Abstract: ATP-sensitive K + channels (KATP) are major component of preventing ischemia-reperfusion injury. However, there is little information regarding to the expressional difference of KATP and its function between left and right ventricles. In this study, we measured the lactate dehydrogenase release of rabbit heart slices in vitro and determined the difference of the KATP expression at the both ventricles by measuring the level of KATP-forming Kir6.2 (OcKir6.2) mRNA using in situ hybridization. The hearts were prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In agreement, a number of studies observed larger I Ks and I to in RV compared with LV. [27][28][29][30] In addition, some studies have observed changes in the gene expression of K ir 6.1/K ir 6.2, underlying the ATP-sensitive K + current (I KATP ), 31,32 NCX1 33 and K ir 2.1/K ir 2.3, molecular components of I K1 . 34,35 Consistent with these molecular data, I K1 density is larger in LV myocytes from guinea pigs, contributing to the stabilisation of the high-frequency rotors in LV.…”
Section: Differences In Ion Channel Propertiesmentioning
confidence: 99%
“…In agreement, a number of studies observed larger I Ks and I to in RV compared with LV. [27][28][29][30] In addition, some studies have observed changes in the gene expression of K ir 6.1/K ir 6.2, underlying the ATP-sensitive K + current (I KATP ), 31,32 NCX1 33 and K ir 2.1/K ir 2.3, molecular components of I K1 . 34,35 Consistent with these molecular data, I K1 density is larger in LV myocytes from guinea pigs, contributing to the stabilisation of the high-frequency rotors in LV.…”
Section: Differences In Ion Channel Propertiesmentioning
confidence: 99%
“…35 Regional heterogeneity between the LV and the RV may also exist for ATP-activated K + current, I KATP . 36,37 In contrast to these electrophysiological studies, a recent proteomic study reported no difference in the expression level of >600 proteins between the RV and the LV from pig and rabbit. Most of these were contractile/structural proteins, oxidative phosphorylation components, and enzymes from intermediary metabolism.…”
mentioning
confidence: 92%
“…In this species, a larger RV I Ks correlates with a higher expression of KCNQ1 and KCNE1, the principal and auxiliary subunit of the I Ks channel, respectively . Regional heterogeneity between the LV and the RV may also exist for ATP‐activated K + current, I KATP …”
Section: Introductionmentioning
confidence: 98%
“…Single-channel currents were sampled at 5 kHz and filtered at 2 kHz using an analog-digital interface (Digidata 1440A, Molecular Devices, USA). Voltage pulse was modified from the ramp protocol used by Choi et al [18]. Experiments were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%